Current understanding of plant-derived exosome-like nanoparticles in regulating the inflammatory response and immune system microenvironment - Qiaoli Yi; Zhijie Xu; Abhimanyu Thakur; Kui Zhang; Qiuju Liang; Yuanhong Liu; Yuanliang Yan (Elsevier, 2023)
Natural compounds are widely used to prevent and treat various diseases due to their antioxidant and anti-inflammatory effects. As a kind of promising natural compound, plant-derived exosome-like nanoparticles (PELNs) are extracted from multivesicular bodies of various edible plants, including vegetables, foods, and fruits, and mainly regulate the cellular immune response to pathogen attacks. Moreover, PELNs could remarkably interfere with the dynamic imbalance between pro-inflammatory and anti-inflammatory effects, facilitating to maintain the homeostasis of cellular immune microenvironment. PELNs may serve as a better alternative to animal-derived exosomes (ADEs) owing to their widespread sources, cost-effectiveness, and easy accessibility. PELNs can mediate interspecies communication by transferring various cargoes such as proteins, lipids, and nucleic acids from plant cells to mammalian cells. This review summarizes the biogenesis, composition, and classification of exosomes; the common separation, purification, and characterization methods of PELNs, the potential advantages of PELNs over ADEs; and the anti-inflammatory and immunomodulatory functions of PELNs in various diseases including colitis, cancer, and inflammation-associated metabolic diseases. Additionally, the future perspectives of PELNs and the challenges associated with their clinical application are discussed.